Association Between Nutrition Social Behavior Change Communication and Improved Caregiver Health and Nutrition Knowledge and Practices in Rural Tanzania - Grant, Frederick Kobina Ebo; Ackatia-Armah, Robert; Okuku, Haile Selassie; Kakuhenzire, Rogers (Frontiers in Public Health, 2022)
Background: Efforts to improve infant and young child feeding practices include the use of nutrition behaviour change communication among caregivers of children under-5-years. We assessed the association between monthly participation in community-level nutrition group meetings on caregiver health and nutrition knowledge and practices (KPs). Methods: Data from community-based cross-sectional survey conducted in Eastern and Southern Highland Zones of Tanzania, were used. Indices were developed for caregivers’ knowledge on nutrition, health-and-childcare, household (HDD) and young child (CDD) dietary diversity, and vitamin A (VA) intakes. Comparison of means and proportions were assessed with Student’s t-test and chi-square test, respectively, between caregivers participating in nutrition group meetings and non-participants. Impact of the number of nutrition meeting attendance on caregiver knowledge and practices scores were examined using multiple regression. Results: Of 547 caregivers surveyed, 49.7% attended nutrition group meetings and received information on nutrition social behavior change communication. Overall, 28% of participating women had a moderate level of nutrition knowledge, 62% had high level of VA knowledge, and 57% had high level of health and childcare knowledge. Participation in nutrition group meetings was significantly associated with health-and-childcare knowledge score, HDD and CDD scores, and household and young child VA intake; magnitude of the associations were greater for caregivers who attended at least four meetings. Conclusions: Findings emphasize the need for programmes that seek to address the issues present in the use of nutrition social behaviour change communication (SBCC) at the community level to improve maternal or caregiver KPs and subsequently, nutrition status of infants and young children.